Mainline mama : a memoir - Harris, Keeonna (Amistad, an imprint of HarperCollins Publishers, 2025)
Keeonna and Jason met as young teens. Only fourteen, Keeonna had never had a boyfriend before, dreamed of attending Spelman to become an obstetrician, and thought she was "grown." Within a year she was pregnant and Jason was in prison, convicted of a carjacking and sentenced to twenty-two years. Overnight Keeonna had become a "mainline mama," a parent facing the task of raising a child--while still growing up herself--with an incarcerated partner.